Aquilaria sinensis leaf tea affects the immune system and increases sleep in zebrafish - Tan, Xiaohui; Wang, Liping; Smith, William Kojo; Sun, Huayan; Long, Lingyun; Mao, Liyan; Huang, Qiuwei; Huang, Huifang; Zhong, Zhaomin (Frontiers in Pharmacology, 2023)
The importance of adequate sleep for good health cannot be overstated. Excessive light exposure at night disrupts sleep, therefore, it is important to find more healthy drinks that can promote sleep under sleep-disturbed conditions. The present study investigated the use of Aquilaria sinensis (Lour.) Spreng leaf tea, a natural product, to reduce the adverse effects of nighttime light on sleep. Here, A.sinensis leaf tea at 1.0 and 1.5 g/L significantly increased sleep time in zebrafish larvae (5-7 dpf) with light-induced sleep disturbance. Transcriptome sequencing and qRT-PCR analysis revealed a decrease in the immune-related genes, such as nfkbiab, tnfrsf1a, nfkbiaa, il1b, traf3, and cd40 in the 1.5 g/L A. sinensis leaf tea treatment group. In addition, a gene associated with sleep, bhlhe41, showed a significant decrease. Moreover, A. sinensis leaf tea suppressed the increase in neutrophils of Tg(mpo:GFP) zebrafish under sleep-disturbed conditions, indicating its ability to improve the immune response. Widely targeted metabolic profiling of the A. sinensis tea using ultra-performance liquid chromatography coupled with electrospray tandem mass spectrometry (UPLC-ESI-MS/MS) revealed flavonoids as the predominant component. Network pharmacological and molecular docking analyses suggested that the flavonoids quercetin and eupatilin in A. sinensis leaf tea improved the sleep of zebrafish by interacting with il1b and cd40 genes under light exposure at night. Therefore, the results of the study provide evidence supporting the notion that A. sinensis leaf tea has a positive impact on sleep patterns in zebrafish subjected to disrupted sleep due to nighttime light exposure. This suggests that the utilization of A. sinensis leaf tea as a potential therapeutic intervention for sleep disturbances induced by light may yield advantageous outcomes.